Analisis pengembangan produk abon ikan tuna menggunakan metode quality function deployment (QFD) - Dhian Herdhiansyah; Sakinah Ambang; Muhammad Syukri; Asriani Asriani; Mariani Mariani (AGROINTEK, 2024)
The study's purpose was to analyze shredded tuna products' development using the Quality Function Deployment (QFD) method. Research subjects are parties involved in shredded tuna fish products' micro—business determination of the number of samples using the Bernoulli formula. as many as 60. QFD analysis stages include: (1) customer requirements analysis: (2) importance level analysis: (3) satisfaction level analysis: (4) goal value analysis (improvement targets to be achieved): (5) improvement ratio analysis: (6) sales point analysis: (7) natural weight analysis: (8) normalized raw analysis (8) technical requirements analysis: (9) technical requirements score analysis: (10) customer requirements score analysis: (11) technical correlation analysis: and (12) analysis of technical correlation scores. The study's results showed that 34 attributes of shredded tuna products were obtained from as many as 11 technical responses proposed in product development. Furthermore, from the 11 technical responses, eight technical answers were obtained that had a significant influence on the product development plan, including: (1) choosing to use easy-to-read fonts/writings; (2) information on the manufacture of packaging designs: (3) information on the nutritional value of shredded tuna fish in the manufacture of new packaging designs; (4) adding to the composition of the ingredients; (5) inspection of the composition and quality of raw materials; (6) the love tagline for Indonesian products in the new packaging design; (7) make packaging designs with new product brands; and (8) the innovation of making shredded tuna with a variety of new flavors.